Pengaruh Bahan Amelioran terhadap Pertumbuhan dan Hasil Tiga Varietas Buncis di atas Sistem Surjan pada Lahan Sulfat Masam Potential - , Koesrini; Eddy William (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
High soil acidity is one of the problems causing low snap bean yield on potential acid sulphate soils. Using tolerant variety and applying ameliorant were several efforts to increase snap bean yield on potential acid sulphate soils. The objective of this research was to evaluate the effect of ameliorant application on plant growth, and yield of three snap bean varieties on potential acid sulphate soils. This research was conducted on potential acid sulphate soil on surjan system at Experimental Station Belandean in Barito Kuala regency of South Kalimantan province in the dry season of 2005. The experiment was arranged in split-plot design with three replications. The main plots were ameliorant application, i.e. control, liming 1 t.ha-1 + manure 2.5 t.ha-1 , and liming 2 t.ha-1 + manure 5 t.ha-1, and the sub plots were three snap bean varieties, i.e. Lebat, Perkasa and Bravo. The result showed that the plant growth and yield of snap bean were affected by ameliorant application. Liming  with dosages of 1.0 t.ha + manure 2.5 t.ha-1 increased yield 2 581 kg.ha-1 or 81.5 % higher than control. All varieties showed the same yield on acid sulphate soil.   Key words:  Ameliorant, snap bean, potential acid sulphate soil